Simulation and serious games for education - Cai, Yiyu; Goei, Sui Lin; Trooster, Wim (Gaming media and social effects., 2017)
This book introduces state-of-the-art research on simulation and serious games for education. The major part of this book is based on selected work presented at the 2014 Asia-Europe Symposium on Simulation and Serious Games held in Windesheim University of Applied Sciences, the Netherlands (Oct 1-2, 2014). It covers three major domains of education applications that use simulation and serious games: Science, Technology, Engineering and Mathematics (STEM) Education; Special Needs Education and Humanity and Social Science Education. Researchers and developers in simulation and serious games for education benefit from this book, and it also offers educators and professionals involved in training insights into the possible applications of simulation and serious games in various areas.